Welcome to Our Hillbrow : A Novel of Postapartheid South Africa - Mpe, Phaswane, 1970-2004 (Book collections on Project MUSE., 2011)
"Welcome to Our Hillbrow is an exhilarating and disturbing ride through the chaotic and hyper-real zone of Hillbrow--microcosm of all that is contradictory, alluring, and painful in the postapartheid South African psyche. Everything is there: the shattered dreams of youth, sexuality and its unpredictable costs, AIDS, xenophobia, suicide, the omnipotent violence that often cuts short the promise of young people's lives, and the Africanist understanding of the life continuum that does not end with death but flows on into an ancestral realm. Infused with the rhythms of the inner-city pulsebeat, this courageous novel is compelling in its honesty and its broad vision, which links Hillbrow, rural Tiragalong, and Oxford. It spills out the guts of Hillbrow--living with the same energy and intimate knowledge with which the Drum writers wrote Sophiatown into being." --